Treatment of pseudo class III malocclusion (Case Report) - Habar, Eddy Heriyanto (Journal of Case Reports in Dental Medicine, 2021)
Objective: This article discusses a case report of a pseudo Class III malocclusion treated with a fixed orthodontic appliance. Methods: Female patient aged 24 with complaints of crossbite in the anterior region and facial aesthetics. The objective examination showed teeth 12, 11, 21, 22 and 23 were crossbite with the antagonist teeth. Patient profile is concave. Result: Orthodontic treatment with fixed orthodontic appliance to align the teeth inside the dental arch to expand the maxillary arch  and reduce the mandibular arch. Conclusion: Maximum results are obtained with appropriate treatment according to the etiology of the case.